UPAYA POLITIK PENGAKUAN HAK PEKERJA MIGRAN DI TINGKAT DESA UNTUK PERLINDUNGAN PEKERJA MIGRAN YANG INKLUSIF - Fifi Kusuma Jayanti; Robi Cahyadi Kurniawan; Tabah Maryanah; Ari Darmastuti (Halu Oleo University, 2025)
This research aims to describe the dynamics of citizenship at the local level, focusing on citizen participation, particularly within the context of liberal citizenship dynamics. It advocates for individual rights to migrate to fulfil the rights of migrant workers, by fostering a shared vision within a local migrant labour community at the village level in East Lampung. This phenomenon represents the configuration of citizenship in East Lampung. The study employs a qualitative descriptive approach, utilising methods such as interviews, surveys, focus group discussions (FGDs), and documentation. The results indicate that citizen participation is facilitated through advocacy efforts carried out by SP Sebay Lampung in collaboration with the Komunitas Perempuan Peduli Buruh Migran (KPPBM) Community. These efforts aim to get the rights of migrant workers to receive protection through policies at the village level.